Effect of Wearing the Elevation Training Mask on Aerobic Capacity, Lung Function, and Hematological Variables - Porcari, John P. (J Sports Sci Med, 2016)
Altitude training and respiratory muscle training (RMT) have been reported to improve performance in elite and well-trained athletes. Several devices (altitude and RMT) have been developed to help athletes gain the competitive edge. The Elevation Training Mask 2.0 (ETM) purportedly simulates altitude training and has been suggested to increase aerobic capacity (VO(2)max), endurance performance, and lung function. Twenty-four moderately trained subjects completed 6 weeks of high-intensity cycle ergometer training. Subjects were randomized into a mask (n = 12) or control (n = 12) group. Pre and post-training tests included VO(2)max, pulmonary function, maximal inspiration pressure, hemoglobin and hematocrit. No significant differences were found in pulmonary function or hematological variables between or within groups. There was a significant improvement in VO(2)max and PPO in both the control (13.5% and 9.9%) and mask (16.5% and 13.6%) groups. There was no difference in the magnitude of improvement between groups. Only the mask group had significant improvements in ventilatory threshold (VT) (13.9%), power output (PO) at VT (19.3%), respiratory compensation threshold (RCT) (10.2%), and PO at RCT (16.4%) from pre to post-testing. The trends for improvements in VT and PO at VT between groups were similar to improvements in RCT and PO at RCT, but did not reach statistical significance (VT p = 0.06, PO at VT p = 0.170). Wearing the ETM while participating in a 6-week high-intensity cycle ergometer training program does not appear to act as a simulator of altitude, but more like a respiratory muscle training device. Wearing the ETM may improve specific markers of endurance performance beyond the improvements seen with interval training alone.